Bifidobacterium animalis subsp. lactis BB-12 Has Effect Against Obesity by Regulating Gut Microbiota in Two Phases in Human Microbiota-Associated Rats - Mao, Kemin; Gao, Jie; Wang, Xianghong; Li, Xiyu; Geng, Shuo; Zhang, Tuo; Sadiq, Faizan Ahmed; Sang, Yaxin (Frontiers in Nutrition, 2022)
Bifidobacterium animals subsp. lactis BB-12 (BB-12) is an extensively studied probiotics species which has been reported to improve the human gut microbiota. This study aimed to confirm the effects of BB-12 on high-fat diet (HFD)-induced gut microbiota disorders. The probiotic BB-12 was consumed by human-microbiota-associated rats and changes in gut microbiota were compared using next generation sequencing of the fecal samples collected from normal chow group, high-fat diet group, and BB-12-supplemented group. The enterotypes switched from Prevotella-dominant to Akkermansia-dominant as a result of switching diet from normal chow to HFD. BB-12 conferred protection on the gut microbiota composition of the rats by increasing the abundance of Prevotella and decreasing the abundance of Clostridium, Blautia, and Bacteroides in 0-3 weeks. In addition, Prevotella-dominant enterotype was maintained, which provides anti-obesity effects. A decrease in body weight and the Firmicutes/Bacteroidetes ratio were also observed at week 3. While in 4-8 weeks, the enrichment of short-chain fatty acids producing bacteria such as Eubacterium and Parabacteroides and probiotics such as Bifidobacterium was observed. The results revealed that BB-12 controls obesity by regulating gut microbiota in two phases. After a short-term intervention, BB-12 supplementation suppressed the transition from the healthy to obesity state by protecting Prevotella-dominant enterotype; whereas, after a long-term intervention, BB-12 ameliorates obesity by enriching beneficial bacteria in the gut.